2022
DOI: 10.1080/2090598x.2022.2026010
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy compared to radical prostatectomy as first-line definitive therapy for patients with high-risk localised prostate cancer: An updated systematic review and meta-analysis

Abstract: Objective To present an update of the available literature on external beam radiation therapy (EBRT) with or without brachytherapy (BT) compared to radical prostatectomy (RP) for patients with high-risk localised prostate cancer (PCa). Methods We conducted a systematic review and meta-analysis of the literature assessing the survival outcomes in patients with high-risk PCa who received EBRT with or without BT compared to RP as the first-line therapy with curative intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Our results support some of the findings of previous reviews and meta-analyses on this topic. For instance, in a study conducted by Abdulmajeed Aydh in 2021, EBRT alone had a significantly worse OS than RP [ 42 ]. The results were also in agreement with a study conducted in 2017 by Omar Fahmy, who also reported a significant improvement in OS in RP-treated patients [ 43 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support some of the findings of previous reviews and meta-analyses on this topic. For instance, in a study conducted by Abdulmajeed Aydh in 2021, EBRT alone had a significantly worse OS than RP [ 42 ]. The results were also in agreement with a study conducted in 2017 by Omar Fahmy, who also reported a significant improvement in OS in RP-treated patients [ 43 ].…”
Section: Reviewmentioning
confidence: 99%
“…The overall HR was found to be HR=0. 42 For radiation therapy: Forest plots for five of the 19 studies were plotted for PCSM in patients treated with RT. Data for the current intervention were extracted from the same studies to ensure an effective comparison between the interventions due to coherence in population demographics.…”
Section: Prostate Cancer-specific Mortalitymentioning
confidence: 99%
“…High‐risk PCa, depending on its definition, is currently detected in 20%–30% of men with clinically localized PCa 3 . While there is still no consensus on the best therapy for these patients, radical prostatectomy (RP) results in durable disease control and excellent survival 2,4–7 . Notably, patients with high‐risk PCa who are diagnosed with lymph node metastases at RP are at an increased risk of PSA failure, metastasis, and death from PCa 2,8 .…”
Section: Introductionmentioning
confidence: 99%
“…3 While there is still no consensus on the best therapy for these patients, radical prostatectomy (RP) results in durable disease control and excellent survival. 2,[4][5][6][7] Notably, patients with high-risk PCa who are diagnosed with lymph node metastases at RP are at an increased risk of PSA failure, metastasis, and death from PCa. 2,8 Identification of the true lymph node status would be helpful to guide the template of lymphadenectomy and/or change the original treatment strategy in a shared decisionmaking process.…”
Section: Introductionmentioning
confidence: 99%